Medium optimization for producing bioactive exopolysaccharides by Agaricus brasiliensis S. Wasser et al. (=A. blazei Murrill ss. Heinem) in submerged culture - Shu, Chin-Hang (Array, 2007)
The effects of media components, including carbon source, KH2PO4, and vitamin B1, on the production and quality of Agaricus brasiliensis S. Wasser et al. (=A. blazei Murrill ss. Heinem) exopolysaccharides (ABEP) were studied in submerged culture. The quality of ABEP was characterized on the basis of their stimulation of the release of tumor necrosis factor-alpha (TNF-α) by macrophage cell line RAW 246.7 and their molecular mass distribution. Glucose was the best carbon source for the production of mycelial biomass and ABEP. The medium composition significantly affected both the relative content of β-(1-3)-glucan and the molecular mass (Mr) in the ABEP and, as a consequence, it also affected the biological activity of ABEP. A medium containing 3.0 g/L of KH2PO4 gave an ABEP of the highest biological activity (1440 pg of TNF-α/mL/5x104 cells), while a medium containing 10 mg/L of vitamin B1 gave an ABEP with a biological activity of 1080 pg of TNF-α/mL/5x104 cells. In a bubble column bioreactor, an optimized medium gave a 1.35-fold increase in ABEP production with a 1.51-fold increase of its biological activity, when compared to the basic medium. This work demonstrates that the relative content of β-(1-3)-glucan in the ABEP is a useful reference indicator of biological activity